Purificação de penicilina G acilase produzida por Escherichia coli e Bacillus megaterium recombinantes - Altarugio, Lucas Miguel (2014)
Penicillin G acylase (PGA) is the key enzyme for the industrial production of β-lactam antibiotics. Major current PGA demand is attended for producer organisms as Escherichia coli and Bacillus megaterium genetically modified. The enzyme produced by Escherichia coli accumulates in the periplasmic space of the bacteria and it requires cell disruption for recovery, whereas the enzyme from Bacillus megaterium is secreted into the production medium. This study aimed to evaluate the adsorption of PGA expressed by these two recombinant microorganisms in cationic and anionic resins for recovery and purification of the enzyme. For E. coli PGA was evaluated ionic adsorption of the enzyme in Streamline SP XL® cation exchanger resin after cell disruption by sonication. In this step, we assessed the influence of pH and buffer, to reduce the loss of enzyme inactivation and adjust the pH to a value suitable for a subsequent selective adsorption of the enzyme. The buffers evaluated were acetate, citrate, phosphate and carbonate, and the values of pH were adjusted between 4,5 and 11,0. No denaturation of the enzyme was observed in buffers and pHs evaluated. However, it was observed enzyme adsorption in cellular debris at pH values equal or smaller than 5,4, this debris adsorption was more apparent in the presence of acetate buffer. Thus, cell disruption was defined at pH 6.0 to prevent loss PGA in the adsorption of debris and adjustment of pH and salt molarity by dilution in the appropriate buffer to prevent denaturation of the enzyme by local reduction of the pH when uses concentrated acid. The STREAMLINE SP XL® resin showed higher adsorption capacity of PGA at pH 5,0 and the temperature range (4 and 25°C) did not influence it. The Langmuir isotherm represented adequately the experimental data of the enzyme adsorption resin at 4 and 25°C (pH 5,0) with similar values of qm and KL 25,4 U/g 185,2 U/g, respectively. Purification of PGA in a fixed-bed column showed overall recovery of activity around 50% and purification factor of about 9 times. The adsorption capacity of cationic resin in this mode of operation was 10,9 UNIPAB/mlresin. The PGA purification secreted by Bacillus megaterium recombinant, produced in a synthetic medium, was studied by ion adsorption resins and the following pH values: Streamline SP XL ® and IMMOBEAD IB-C435 (cation-exchanger resins, pH 5,0, 5,5 and 6,0); manae-agarose activated with 40 and 80mmoles/g amino groups (cation exchanger resin, pH 6,0, 7,0 and 7,5); STREAMLINE DEAE XL® and STREAMLINE Q XL® (anionic exchange resins, pH 7,5 and 8,5). Equilibrium experiments in cationic resins Streamline SP XL ® (4°C, pH 5,0) and IB-C435 IMMOBEAD (4°C, pH 5,5) allowed estimation of the parameters of the Langmuir model qm = 76,6 and 91,5 U/g KL = 294,7 and 412,3 U/g, respectively. Despite the high adsorptive capacity of these resins, they were not suited to purification of PGA, because their adsorbes PGA and the contaminants. Manae-agarose resins (40 and 80 μmoles/g) were not effective in PGA adsorption. The STREAMLINE anionic exchangers resins not adsorbed significant amount of PGA in pH evaluated, however, this resin performed a adsorption of almost of 50% proteins present in the medium, demonstrating selective for removal contaminating proteins. Adsorption assays in fixed-bed column Streamline Q XL ® (22°C, pH 8,0) showed that the resin is effective in adsorption of contaminating proteins, it is possible to recover approximately 70 % PGA with a purification factor of 4 times and high specific activity of about 25 U/mg. Already on STREAMLINE SP XL® (22ºC, pH 5,0) resin, the total enzyme recovery was 70 %, but with a purification factor of only 1,61 times and specific activity of around 11 U/mg. It was concluded that adsorption in anionic mode is more advantageous, because presents a better performance and avoid the enzyme dilution. The cultivation of recombinant B. megaterium in a high cell density bioreactor using complex medium, allowed to reach PGA volumetric activity of 50 U/mL. After concentration of the enzyme extract by ultrafiltration to 100 U/mL, was evaluated purification of the enzyme on gel filtration resin column using Superdex 200 Prep Grad (22 °C, pH 7,5). This technique allowed high enzyme recovery (>93%), however with a purification factor of 3 times and specific activity of 13 U/mg.